2000
DOI: 10.1007/s007050070010
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses and cytokine induction in the development of severe hepatitis during acute infections with murine cytomegalovirus

Abstract: Salivary gland-derived murine cytomegalovirus (SGV) infections of mice have been widely used as models of human cytomegalovirus infections and in the study of CMV biology. Still, many aspects of SGV pathogenesis are not clearly defined. Fatal and non-fatal SGV infections were investigated to characterize pathogenetic correlates of mortality and to assess the role of the immune response in disease progression. Suppression of immune responses was observed in both lethal and sublethal infections. Depletion of imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 43 publications
3
47
1
Order By: Relevance
“…Additional studies have demonstrated that CD8 T cells accumulate in the liver following infection with MCMV (12,19,20,48,51); however, this is the first report documenting the mechanisms required for promoting their recruitment and that of MCMV-specific CD8 T cells. Our results show a clear induction of CXCL9 and CXCL10 protein in the liver during MCMV infection.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Additional studies have demonstrated that CD8 T cells accumulate in the liver following infection with MCMV (12,19,20,48,51); however, this is the first report documenting the mechanisms required for promoting their recruitment and that of MCMV-specific CD8 T cells. Our results show a clear induction of CXCL9 and CXCL10 protein in the liver during MCMV infection.…”
Section: Discussionmentioning
confidence: 77%
“…It is speculated that CXCL9 induction reflects the innate NK cell-mediated IFN-␥ effects (37,40,41,43,50), as this chemokine is highly dependent on IFN-␥ for production (53,56). However, CXCL10 can be in- duced by IFN-␥ in addition to other molecules, including tumor necrosis factor alpha, which is found in the liver during MCMV infection (20,33,36,51). In addition, as antibody neutralization of these CXCR3 ligands reduced the proportions and total numbers of hepatic MCMV-specific CD8 T cells, it is probable that the combined effects of these chemokines initiate the CD8 T-cell inflammatory response but CXCL10 may exert distinct functions during late acute MCMV infection in the liver that remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Infection of mice with MCMV mimics virus-induced disease in humans in terms of presenting a large spectrum of clinical manifestations. For example, high viral titres in target organs are associated with pneumonitis, 50 hepatitis 51 and retinitis. 52,53 Moreover high viral titres in the spleen or liver may lead to fatal infection.…”
Section: Mouse Models Of CMV Infectionmentioning
confidence: 99%